`RESISTENSI PROGRAM PEMBERDAYAAN PEMUKIMAN ORANG RIMBA DI TAMAN NASIONAL BUKIT DUABELAS JAMBI - Rina Astarika; Partini Partini; Endang Sulastri (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
Jambi Province Government has empowered Rimba people in various fields. The empowerment involves all relevant stakeholders namely Government, Private Sector and NGOs. The success of empowerment in the field of settlement has not been standardized. This study aims to examine the resistance of the settlement empowerment program on Rimba people in Bukit Duabelas National Park of Jambi (BDNP). The research method used was qualitative-descriptive. The research data was obtained through direct observation, focus group discussion, interviews, observation, documentation and literature studies. The results of the study indicate that the resistance of settlement empowerment program of Rimba people in Jambi National Park is due to 1) settlement empowerment does not refer to Rimba people social, economic and cultural characteristics, or it can be said that empowerment is not in accordance with Rimba people system of housing and cultural development concepts. 2) the empowerment of settlements were not accompanied by economic empowerment of Rimba people 3) the failure of the concept of the fostering remote indigenous communities settlement as a comprehensive institution 4) There is still lack of cross-sectorial cooperation in empowering settlements for Rimba people. Keyword: resistance, empowerment, settlements, Rimba people- NPBD